INTEGRATING VALUES-ORIENTED DEEP LEARNING TO PROMOTE GLOBAL CITIZENSHIP ATTITUDES AMONG PRIMARY LEARNERS: MENGINTEGRASIKAN PEMBELAJARAN DALAM (DEEP LEARNING) BERORIENTASI NILAI UNTUK MENINGKATKAN SIKAP KEBANGSAAN GLOBAL DI KALANGAN SISWA SEKOLAH DASAR - Risma Inayatur Amaliyah; Muhlasin Amrullah; Mahardika Darmawan Kusuma Wardana (SOSIOEDUKASI, 2026)
This study aims to analyze the effect of applying deep learning integrated with the values of QS. Al-Hujurat verses 9–13 on strengthening elementary school students' attitudes toward global diversity. The study uses a quantitative approach with a one-group pretest–posttest pre-experimental design. The research subjects consisted of 34 fifth-grade students at SDN Wonoplintahan 2. The research instrument was a global diversity attitude test that included indicators of empathy, tolerance, appreciation of differences, solidarity and cooperation, and global responsibility. The Shapiro–Wilk normality test, paired sample t-test, and Eta effect size were used to analyze the data. All analyses were conducted using SPSS 25. The results showed a significant increase in global diversity attitude scores after the intervention, with a large effect size and a significance value of 0.000 (<0.05). These results indicate that QS. Al-Hujurat can effectively and sustainably shape the global diversity attitudes of elementary school students.